Anxiety, Health Self-Perception, and Worry About the Resurgence of COVID-19 Predict Fear Reactions Among Genders in the Cuban Population - Yunier Broche-Pérez; Yunier Broche-Pérez; Zoylen Fernández-Fleites; Zoylen Fernández-Fleites; Evelyn Fernández-Castillo; Evelyn Fernández-Castillo; Elizabeth Jiménez-Puig; Elizabeth Jiménez-Puig; Annia Esther Vizcaíno-Escobar; Dunia M. Ferrer-Lozano; Lesnay Martínez-Rodríguez; Reinier Martín-González (Frontiers Media S.A., 2021)
The resurgence of COVID-19 could deepen the psychological impacts of the pandemic which poses new challenges for mental health professionals. Among the actions that should be prioritized is the monitoring of the groups that have shown greater psychological vulnerability during the first stage of the pandemic. The first aim of our study is to explore the fear reactions to COVID-19 between genders during the second wave of the outbreak in Cuba. Second, establish possible predictors of fear of COVID-19 in relation to gender. Specifically, we will evaluate how anxiety related to COVID-19, health self-perception, and worry about the resurgence of COVID-19 predict fear reactions among women and men in the Cuban population. A cross-sectional online study was designed. The research was conducted between August 16 and October 18, 2020. A total of 373 people completed the online survey. A socio-demographic questionnaire, the Fear of COVID-19 Scale and the Coronavirus Anxiety Scale were used. An independent-samples t-test was conducted to compare the fear, worry, anxiety and self-perceived health scores, between genders. The relationship between those variables and fear of COVID-19, was investigated using Pearson correlation coefficient. Finally, multiple linear regression was used to evaluate the possible associations (predictors) related to fear of COVID-19. In our study, women, compared to men, presented greater fear reactions, greater concern about resurgence of COVID-19 and poorer self-perceived health. Anxiety reactions in our sample showed no differences between genders. In women, anxiety of COVID-19, worry about resurgence of COVID-19, and self-perceived health are associated with fear reactions to COVID-19. In the case of men, the self-perceived health showed no associations with fear reactions. Our results confirm the results of several related investigations during the first wave of the pandemic where women have shown greater psychological vulnerability compared to men. However, we cannot rule out that the real impact of the pandemic on mental health in men is much greater than that described by the studies conducted to date. Additional studies are needed on the psychological impact of COVID-19 on men.